How can we harness quantitative genetic variation in crop root systems for agricultural improvement?. Issue 3 (11th March 2016) - Topp, Christopher N.; Bray, Adam L.; Ellis, Nathanael A.; Liu, Zhengbin
Abstract: Root systems are a black box obscuring a comprehensive understanding of plant function, from the ecosystem scale down to the individual. In particular, a lack of knowledge about the genetic mechanisms and environmental effects that condition root system growth hinders our ability to develop the next generation of crop plants for improved agricultural productivity and sustainability. We discuss how the methods and metrics we use to quantify root systems can affect our ability to understand them, how we can bridge knowledge gaps and accelerate the derivation of structure‐function relationships for roots, and why a detailed mechanistic understanding of root growth and function will be important for future agricultural gains. Abstract : This review article focuses on technologies and methodologies that allow us to measure root systems, the "hidden‐half" of plants, and how we can utilize them to develop more stress resistant crop plants with fewer resources.